The Party Identification of Germany's Immigrant Population: Parties Should Not Fear Eased Naturalization Requirements - Martin Kroh; Ingrid Tucci (Weekly Report, 2010)
Individuals with a migration background represent a steadily increasing percentage of Germany's population. Although the majority of individuals with migration background lack German citizenship and are therefore unable to vote, the number of naturalized immigrants continues to rise. Accordingly, political parties have been showing greater interest in this group of potential voters. Data from the German Socio-Economic Panel Study (SOEP) show that individuals with migration background develop diverse orientations to Germany's political parties in relation to their country of origin. The effect exercised by the country of origin is still present after many years of residence in Germany and among the second-generation. A large majority of individuals from the so-called "recruitment countries"-i.e. countries from which Germany acquired workers for its booming economy in the 1950s and 60s; namely, Turkey, Yugoslavia, Spain, Italy, Greece, and Portugal-identify politically with the SPD (Germany's mainstream labor party). By contrast, foreigners of German descent who have immigrated from Eastern Europe and Russia (so-called "Aussiedler" or "Spätaussiedler") tend to support the CDU/CSU (Germany's traditional conservative party alliance). Germany's smaller political parties find relatively little support among immigrants and their offspring. While extremely diverse party identifications are witnessed among migrants depending on their country of origin, these differences can only be minimally attributed to social circumstances or basic ideological outlook. Model calculations show that eased naturalization laws would not provide an appreciable advantage to any single political party.
Keywords: Z13; P16; J15; 330; Migrants; Political behavior; SOEP